INTEGRATING ETHICAL COMMUNICATION AND INFORMATION LITERACY IN AQIDAH-AKHLAQ LEARNING: A STRATEGY FOR ISLAMIC CHARACTER FORMATION AT DARUL QUR’AN ISLAMIC BOARDING SCHOOL - Wahyudi, Wahyudi; Zainun, Zainun; Kamalia, Kamalia (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study investigates the integration of ethical communication values into the Aqidah-Akhlaq curriculum to foster Islamic character development among students at MTs Darul Qur’an, an Islamic boarding school in Medan, Indonesia. Using a descriptive qualitative method, the research explores students’ daily communication behaviors, the pedagogical roles of teachers and guardians, and the strategic incorporation of information literacy. Findings reveal a significant gap between moral instruction and students' interpersonal conduct, often manifested through disrespectful interactions and communication breakdowns. However, when Aqidah-Akhlaq is delivered through dialogical, participatory methods, and supported by role modeling, students exhibit increased ethical awareness and engagement. The study emphasizes that information literacy must be repositioned as a core moral and pedagogical framework rather than a supplementary skill. It concludes with a call for institutional reform and teacher capacity building to embed communication ethics within Islamic education.